Prevalence of Blood Group A2 in Northern Pakistan - Yazdani, Muhammad Sajid; Khalid, Zeeshan; Rathore, Muhammad Ali; Fatimah, Sarah (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the prevalence of A1 and A2 subgroups of blood group A in healthy blood donors of northern Pakistan.Study Design: Cross sectional study.Place and Duration of Study: Armed Forces Institute of Transfusion, Rawalpindi Pakistan, from Sep to Dec 2017.Methodology: The blood samples of donors reported during the study period at Armed Forces Institute of Transfusion were collected. ABO typing was performed and those in group A and AB were further subtyped using anti-A1 lectin and thus the individuals were labelled as A1 (and A1B) or A2 (and A2B). The serum of individuals with groups A2 and A2B was tested for anti-A1 based on the reaction with A1 red cells.Results: Out of total 4485 donors, 1116 (24.88%) were of blood group A and 422 (9.41%) individuals were of AB group. Out of 146 (13.08%) individuals among 1116 blood group A donors were of subgroup A2. While out of 422 of blood group AB, 80 (18.95%) were A2B. 21 (14.38%) out of 146 individuals of A2 blood group, had anti-A1 antibody while among 80 individuals with A2B blood group only 2 (2.50%) had anti-A1 antibody in their serum.Conclusion: Blood group A2 is quite prevalent in our population. Although anti-A1 is present in significant fraction of A2 blood group individuals, the routine testing is not needed to identify the A2 group and cross match compatibility is the only requirement as anti-A1 is rarely active at 37° C.